MAKNA KONTEKSTUAL ~TEKURERU DAN ~TEYARU DALAM NOVEL BOTCHAN - Wiyatasari, Reny (KIRYOKU, 2017)
The problem in this research is the contextual meaning of ~tekureru and ~teyaru (~teageru) usage. This research is a descriptive case study on Japanese novel of Botchan which applied purposive sampling. The data were collected by employing observation method through note-taking techniques. The data were analysed by using componential analysis of Spradley.The result of research shows that : ~tekureru and ~teyaru (~teageru) have beneficial meaning and disadvantageous meaning. The supporting verb of ~tekureru have beneficial meaning and disadvantageous meaning beside thanking meaning.. The usage of supporting verb ~teyaru (~teageru) not only  has beneficial meaning, but also have disadvantageous meaning when it’s usage give a bad influence on listener or on p.